Short-term ageing study on the palm oil and mineral oil in the presence of insulation paper, moisture, low molecular weight acid, and oxygen - Mustam, Muhammad Muzamil; Azis, Norhafiz; Jasni, Jasronita; Halis, Rasmina; Talib, Mohd Aizam; Yunus, Robiah; Abdul Raof, Nurliyana; Yaakub, Zaini (Universiti Putra Malaysia Press, 2023)
This study presents the short-term ageing study on refined, bleached and deodorised palm oil (RBDPO) and mineral oil (MO) in the presence of insulation paper, moisture, low molecular weight acid (LMA) and oxygen. The ageing experiment was performed for 7 days at 140°C. The oil was maintained dried while the paper’s moisture was varied between 0.5% and 3.5%. In total, 0.2 g of LMA and 20 mbar of oxygen pressure were initially introduced in the oil before the ageing started. Several analyses were conducted after the ageing experiment, which include the AC breakdown voltage (BDV) oil/paper, tensile strength, degree of polymerization (DP) and thermogravimetric analysis and differential scanning calorimetry (TGA-DSC). After being subjected to ageing in the presence of LMA and oxygen, the reduction of AC BDV of RBDPO is lower than MO at all moisture levels. At the same condition, the AC BDV of RBDPO-impregnated paper also maintains higher than MO-impregnated paper. The RBDPO-impregnated paper, in the presence of LMA and oxygen, has higher resistance toward ageing than MO-impregnated paper based on DP and tensile index, even in high moisture. All RBDPO are more resistant to ageing than MO in the presence of LMA and oxygen based on the high onset temperatures of the TGA-DSC analysis.